Analisis Penentuan Komoditas Unggulan Sektor Pertanian dalam Pengembangan Wilayah: Studi Kasus di Kecamatan Bayah Kabupaten Lebak - Selfi Nor Amalia Istiqomah; Mujio Mujio; Janthy T Hidayat (Jurnal Zona, 2024)
Regional development is a partial or comprehensive movement to improve the function of land and the structuring of social, economic, cultural, educational, and welfare of the community to advance the region. The importance of commodities in regional development is closely related to key factors such as economic growth, increase in farmers' income, food security, infrastructure development, economic diversification, natural resource management, increasing competitiveness, and strengthening institutions and policies, all of which contribute to community welfare and environmental sustainability. The goals of superior commodities are to increase local economic growth, increase farmers' incomes, achieve food security, encourage infrastructure development, diversify the economy, manage natural resources sustainably, increase competitiveness in the market, and strengthen institutions and policies that support the agricultural sector. Therefore, it is necessary to research the development of superior commodities in Bayah District with the research title "Determination of Superior Commodities in the Agricultural Sector in Regional Development in Bayah District, Lebak Regency." This research will focus on superior commodities that can encourage economic growth in Bayah District, with the identification of food crop base commodities, analysis of food crop superior commodities, and the formulation of food crop superior commodity development strategies in Bayah District. The research uses Location Quotient (LQ) analysis to find base commodities that can be the main focus in regional development with a superior commodity-based approach. The results of LQ analysis show that the leading commodities in Bayah District are rice and soybeans. However, multicriteria analysis shows that rice has a significant contribution to added value and economic benefits in Bayah District. Based on the results of problem solving, it is concluded that to increase a significant contribution to agricultural development in Bayah District, it is necessary to focus on rice superior commodities to expand the use of agriculturalÂ land.